Distribution of circular proteins in plants: large-scale mapping of cyclotides in the Violaceae - Burman, Robert; Yeshak, Mariamawit Y.; Larsson, Sonny; Craik, David J.; Rosengren, K. Johan; Göransson, Ulf (Frontiers in Plant Science, 2015)
During the last decade there has been increasing interest in small circular proteins found in plants of the violet family (Violaceae). These so-called cyclotides consist of a circular chain of approximately 30 amino acids, including six cysteines forming three disulfide bonds, arranged in a cyclic cystine knot motif. In this study we map the occurrence and distribution of cyclotides throughout the Violaceae. Plant material was obtained from herbarium sheets containing samples up to 200 years of age. Even the oldest specimens contained cyclotides in the preserved leaves, with no degradation products observable, confirming their place as one of the most stable proteins in nature. Over 200 samples covering 17 of the 23 genera in Violaceae were analysed, and cyclotides were positively identified in 150 species. Each species contained a unique set of between one and 25 cyclotides, with many exclusive to individual species. We estimate the number of different cyclotides in the Violaceae to be 5,000-25,000, and propose that cyclotides are ubiquitous among all Violaceae species. Twelve new cyclotides from eight phylogenetically dispersed genera were sequenced. Furthermore, the first glycosylated derivatives of cyclotides were identified and characterized, further increasing the diversity and complexity of this unique protein family.